(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Dan Solomon articulates a compelling critique of the rationalist architectural modernism – what he calls the “City of Hope” – that dominated urban design for much of the 20th century. His answer, the “City of Love,” prizes particularity and sensitivity to physical, social, and historic contexts, and has become a new planning orthodoxy, particularly in the San Francisco Bay Area. But the City of Love takes longer and costs more. It is careful, sensitive, seeks to do no harm, and defaults to inaction. While these are valid principles in response to the excesses of Modernism, they do not provide an urban program capable of meeting the mounting urban crises of housing, homelessness, and climate change.